Impaired mitochondrial function of alveolar macrophages in carbon nanotube-induced chronic pulmonary granulomatous disease. (1st December 2020) - Soliman, Eman; Elhassanny, Ahmed E.M.; Malur, Anagha; McPeek, Matthew; Bell, Aaron; Leffler, Nancy; Van Dross, Rukiyah; Jones, Jacob L.; Malur, Achut G.; Thomassen, Mary Jane
Highlights: MWCNT induces chronic pulmonary granulomatous inflammation. MWCNT reduces mitochondrial fatty acid oxidation in alveolar macrophages. MWCNT induces pulmonary oxidative stress and apoptosis. MWCNT increases miR-27b expression in alveolar macrophages. Abstract: Human exposure to carbon nanotubes (CNT) has been associated with the development of pulmonary sarcoid-like granulomatous disease. Our previous studies demonstrated that multi-walled carbon nanotubes (MWCNT) induced chronic pulmonary granulomatous inflammation in mice. Granuloma formation was accompanied by decreased peroxisome proliferator-activated receptor gamma (PPARγ) and disrupted intracellular lipid homeostasis in alveolar macrophages. Others have shown that PPARγ activation increases mitochondrial fatty acid oxidation (FAO) to reduce free fatty acid accumulation. Hence, we hypothesized that the disrupted lipid metabolism suppresses mitochondrial FAO. To test our hypothesis, C57BL/6 J mice were instilled by an oropharyngeal route with 100 μg MWCNT freshly suspended in 35 % Infasurf. Control sham mice received vehicle alone. Sixty days following instillation, mitochondrial FAO was measured in permeabilized bronchoalveolar lavage (BAL) cells. MWCNT instillation reduced the mitochondrial oxygen consumption rate of BAL cells in the presence of palmitoyl-carnitine as mitochondrial fuel. MWCNT also reduced mRNA expression of mitochondrial genes regulating FAO, carnitine palmitoyl transferase-1 (CPT1), carnitine palmitoyl transferase-2 (CPT2), hydroxyacyl-CoA dehydrogenase subunit beta (HADHB), and PPARγ coactivator 1 alpha (PPARGC1A). Importantly, both oxidative stress and apoptosis in alveolar macrophages and lung tissues of MWCNT-instilled mice were increased. Because macrophage PPARγ expression has been reported to be controlled by miR-27b which is known to induce oxidative stress and apoptosis, we measured the expression of miR-27b. Results indicated elevated levels in alveolar macrophages from MWCNT-instilled mice compared to controls. Given that inhibition of FAO and apoptosis are linked to M1 and M2 macrophage activation, respectively, the expression of both M1 and M2 key indicator genes were measured. Interestingly, results showed that both M1 and M2 phenotypes of alveolar macrophages were activated in MWCNT-instilled mice. In conclusion, alveolar macrophages of MWCNT-instilled mice had increased miR-27b expression, which may reduce the expression of PPARγ resulting in attenuation of FAO. This reduction in FAO may lead to activation of M1 macrophages. The upregulation of miR-27b may also induce apoptosis, which in turn can cause M2 activation of alveolar macrophages. These observations indicate a possible role of miR-27b in impaired mitochondrial function in the chronic activation of alveolar macrophages by MWCNT and the development of chronic pulmonary granulomatous inflammation.